The role of intellectual property rights and packagе safety features in the prevention of counterfeit medicines - Ancevska Netkovska, Katerina; Brezovska, Katerina; Geškovski, Nikola; Tonić Ribarska, Jasmina; Petrovska Jakimovska, Biljana; Achevski, Blagoj; Goračinova, Katerina (Archives of Pharmacy, 2020)
The fast growth of counterfeiting medicines in the last two decades has created one of the biggest problems facing the pharmaceutical industry on the global level, resulting in loss of income, product withdrawal, loss of brand value, etc. But this is not only the problem of the intellectual property rights of the pharmaceutical industry, it is also the problem of the healthcare regulatory authorities, whose most significant concern is the risk to the public health. Pharmaceutical manufacturers, together with the wholesalers and retailers, have an essential role in the fight against counterfeit medicines by the implementation of different anti-counterfeit technologies for securing the supply-chain of medicines. The protection of drug packaging has a specific role in the drug development process, as well as in the fight against counterfeit medicine. The authenticity of the medicine and the forensic elements for protection on the packaging may be confirmed using different technologies. Tracking and tracing of pharmaceutical products in the supply chain, keeping electronic records for all stages of the distribution, and verification of the authenticity of a medicinal product is a key element and an effective solution for timely detection of counterfeit medicines and protection of intellectual property rights.
Keywords: intellectual property rights; counterfeiting; medicines; drug packaging